(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The present investigation is fundamentally worried about a few new sorts of fixed point theorems in various spaces, for example, cone metric spaces and fuzzy metric spaces. By utilizing these acquired fixed point theorems, we at that point demonstrate the presence and uniqueness of the solutions to two classes of two-point customary differential equation problems.The principle point of this examination is to introduce the idea of general Mann and general Ishikawa write twofold sequences iterations with blunders to approximate fixed points. We demonstrate that the general Mann compose twofold sequence iteration process with blunders meets strongly to a fortuitous event point of two continuous pseudo-contractive mappings, each of which maps a bounded shut arched nonempty subset of a genuine Hilbert space into itself. In addition, we talk about equality from the S, T-secure qualities point of view under specific confinements between the general Mann write twofold sequence iteration process with mistakes and the general Ishikawa iterations with blunders. An application is additionally given to help our thought utilizing good compose mappings.